Finding a place for boomtowns in energy geographies. Issue 2 (30th May 2018) - Woodworth, Max D.
Abstract : Energy boomtowns are a persistent feature of the modern era. Yet such cities have been neglected in energy geography research, despite a remarkable invigoration of the subfield in recent years. Drawing on examples from around the world as well as historical examples, this paper argues that energy boomtowns are a vital feature of the expansive geographies of energy uses. It further argues that energy boomtowns must be seen as the confluence of four areas or dimensions: regional transformation; conflicts in city politics, governance and planning; legitimation of carbon economies; and social disruption. Each of these reveals the social production of energy and the frequently contentious process of urban space production. While the recurring emergence of energy boomtowns is of empirical interest, the turbulent setting of the boomtown can also reveal much about the social stakes of energy uses through their intersections with place‐specific, urban‐focused development agendas.